Realising the environmental benefits of metal–organic frameworks: recent advances in microwave synthesis - Thomas-Hillman, Ieuan; Laybourn, Andrea; Dodds, Chris; Kingman, Samuel W. (Royal Society of Chemistry, 2018)
Metal–organic frameworks (MOFs) are a broad class of porous crystalline materials that show great potential for a wide-range of applications in areas such as energy and environmental sustainability. MOFscan show significant advantages in gas selectivity and separation over traditional adsorbents such as zeolites and activated carbons since they are tuneable both in terms of porosity and chemical functionality. The ability to control the pore environment of the MOF is one of their remarkable advantages and affords control over the structure and properties required for specific applications. Despite these advantages, the industrial adoption of MOFs is slow owing to the paucity of scalable, environmentally sustainable manufacturing methods and higher costs compared to zeolites. Microwave (MW) technology is an extremely promising method of MOF production owing to significantly reduced reaction times and subsequently lower process energy consumption, control over MOF properties, and the ability to produce MOFs and MOF-hybrids otherwise difficult to isolate or unobtainable through other synthetic routes. However, the ability to produce the multiple kilogram or even tonne quantities of MOFs required by industry using MW technology is yet to be achieved owing to little or no understanding of the interaction(s) of reactants and MOFs with the electric field, and crucially, how this informs the design of the scale up processes. This review aims to bridge this gap in knowledge by (1) highlighting recent advances in understanding of MW–MOF interactions and areas for future focus; (2) providing an up-to-date and comprehensive summary of literature on MW synthesis of MOFs, focusing on examples where MW heating has facilitated novel and unique results in the laboratory; and (3) emphasising the advantages, challenges and current steps and methodologies required towards industrial-scale MW production of MOFs.